(untitled) (Journal of Education and Development, 2017)
Teachers across the world have become barraged with various techniques to meet the educational needs of multiple subgroups, e.g., autistic, behavior disorders, English Language Learners (ELL), gifted. They have the responsibility of creating environments in which learners become more knowledgeable and skilled from the time when they entered the classroom. For the current and future generations of learners and their teachers, the emergence of technology has created new prospects for accommodating the learning styles of diverse classrooms. The versatility of technology can be used to organize and design material that promotes successful acquisition and retention of expected middle school content within the inclusive settings. In this paper, the authors provide a greater understanding of how technology can be an effective change agent for learning in middle school inclusive settings. Suggestions are included for teachers’ capacity building to integrate technology to accommodate diverse student learning needs and styles.